Synthesis, in vitro, and in silico evaluation of new carbohydrazide and 1,3,4-oxadiazole linked Bis-indoles as antidiabetic agents - Sengul, Ibrahim F.; Kocaman, Kubra; Bingul, Murat; Zengin, Irem N.; Sahin, Hasan; Saglam, Mehmet F.; Kandemir, Hakan (Elsevier, 2025)
A range of indole-2-carboxylates was successfully prepared via the Hemetsberger reaction using commercially available benzaldehyde derivatives. The indole-2-carboxylates were then converted to the corresponding indole2-carbohydrazides, which were then reacted with indole-2-carbonyl chloride to generate carbohydrazide-linked bis-indoles. Furthermore, a cyclodehydration reaction of the bis-indole carbohydrazides yielded asymmetrical 1,3,4-oxadiazole-linked bis-indoles. The biological potency of the targeted compounds was evaluated towards the alpha-glucosidase, alpha-amylase enzymes and the structure-activity relationship study was also discussed for the determination of new candidates as anti-diabetic agents. The molecules represented higher sensitivity for the inhibition of alpha-glucosidase enzyme, even better IC50, values were observed than the standard Acarbose, ranging from 69.2 to 251.9 mu M. However, alpha-amylase enzyme was more resistant to synthetized compounds and lower inhibition activity was detected with the collected IC50 data. The presence of oxadiazole ring increased the potency with the maximum interactions, reported as 2D interactions in the molecular docking section, observed on the binding sites of the enzymes and also electron withdrawing substitutions were also helped to obtain the highest potency for both enzyme inhibitions.
Keywords: Bis-indole; 1,3,4-oxadiazole; Carbohydrazide; alpha-Glucosidase; alpha-Amylase; In Silico